2015
DOI: 10.3389/fimmu.2015.00401
|View full text |Cite
|
Sign up to set email alerts
|

CD1d- and MR1-Restricted T Cells in Sepsis

Abstract: Dysregulated immune responses to infection, such as those encountered in sepsis, can be catastrophic. Sepsis is typically triggered by an overwhelming systemic response to an infectious agent(s) and is associated with high morbidity and mortality even under optimal critical care. Recent studies have implicated unconventional, innate-like T lymphocytes, including CD1d- and MR1-restricted T cells as effectors and/or regulators of inflammatory responses during sepsis. These cell types are typified by invariant na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 253 publications
(285 reference statements)
3
38
0
Order By: Relevance
“…iNKT-cells play key regulatory roles in a diversity of diseases including viral and bacterial infections, cancer surveillance and autoimmune diseases(1-3, 6). It is being increasingly demonstrated that iNKT-cells play a key role in coordinating this immune response in both experimental sepsis as well as in critically ill septic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…iNKT-cells play key regulatory roles in a diversity of diseases including viral and bacterial infections, cancer surveillance and autoimmune diseases(1-3, 6). It is being increasingly demonstrated that iNKT-cells play a key role in coordinating this immune response in both experimental sepsis as well as in critically ill septic patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike thymic NKT cells, non-thymic NKT-cells do not require ongoing CD1d interaction for homeostasis, proliferation or survival in their tissue beds(30). Rather, the cytokine milieu as well as the tissue locale in which the iNKT-cells are found, liver versus spleen, may be just as important in influencing iNKT-cell function(3, 27, 30, 31). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have implicated 2 distinct unconventional, innate-like T lymphocytes, such as MR1-restricted mucosal-associated invariant T (MAIT) cells and CD1d-restricted natural killer T (NKT) cells as effectors and/or regulators of inflammatory responses during sepsis (4). These cell types express an invariant T cell receptor (TCR) Vα7.2-Jα33 chain paired with a limited repertoire of Vβ chains or an invariant TCR pair of Vα24-Jα18/Vβ11 chains together with the Vβ chain, respectively (5).…”
Section: Introductionmentioning
confidence: 99%
“…110 On the other hand, the impact of the microbiota is not limited to the mucosal surfaces and can influence apparently any part of the body, including seemingly remote areas, such as the brain. 111 With regard to iNKT cells, the above-mentioned systemic effects of antibiotic treatment and the role of iNKT cells are relevant in sepsis, 112 which is often caused by translocated intestinal bacteria. 113 Furthermore, one member of the commensal Sphingobium species (Novosphingobium aromaticivorans) has been linked to iNKT celldependent autoimmune responses against the bile duct in mice 53 and humans.…”
Section: Discussionmentioning
confidence: 99%